(untitled) (International Journal of Animal Biodiversity, Conservation and Systematics ( IJABC), 2023)
Conservation prioritisation — the allocation of limited resources to maximise biodiversity outcomes across competing sites, species, and actions — is inherently a multi-criteria decision problem involving ecological, economic, social, and political dimensions that cannot be optimised simultaneously. This study developed and validated a Multi-Criteria Decision Model (MCDM) framework for vertebrate conservation prioritisation integrating five criteria — extinction risk (IUCN status), irreplaceability (complementarity-based), cost-effectiveness (cost per species protected), climate vulnerability (trait-based), and social co-benefits (community livelihood value) — using three weighting methods: equal weights, Analytic Hierarchy Process (AHP) stakeholder-derived weights, and entropy-based objective weights. The framework was applied to a dataset of 284 terrestrial vertebrate species across 48 candidate protected area sites in the Mediterranean Basin biodiversity hotspot, with conservation cost data from national land acquisition records. MCDM priority rankings were compared against: (i) single-criterion rankings by IUCN status alone; (ii) systematic conservation planning output from Marxan v4.0; and (iii) expert-elicited priority rankings (n = 42 conservation practitioners). The three MCDM weighting approaches produced moderately correlated priority rankings (Spearman rs = 0.68–0.82 between methods), substantially outperforming IUCN-only rankings (rs = 0.44–0.56 vs. expert consensus). MCDM and Marxan rankings were significantly correlated (rs = 0.74, p < 0.001) but diverged meaningfully for 12 sites where cost-effectiveness and social co-benefit criteria drove re-ranking. Sensitivity analysis confirmed that extinction risk (weight elasticity 0.42) and irreplaceability (0.38) were the criteria most influential on priority outcomes, while social co-benefits showed the highest stakeholder weight variation (CV = 0.48). The MCDM framework provides a transparent, stakeholder-inclusive alternative to single-criterion prioritisation that better reflects the multi-dimensional nature of real-world conservation decision-making under the Convention on Biological Diversity Kunming-Montreal Global Biodiversity Framework.